Population-level adult mortality following the expansion of antiretroviral therapy in Rakai, Uganda. (2nd January 2020) - Nabukalu, Dorean; Reniers, Georges; Risher, Kathryn A.; Blom, Sylvia; Slaymaker, Emma; Kabudula, Chodziwadziwa; Zaba, Basia; Nalugoda, Fred; Kigozi, Godfrey; Makumbi, Fred; Serwadda, David; Reynolds, Steven J.; et al.
Abstract : There are limited data on the impact of antiretroviral therapy (ART) on population-level adult mortality in sub-Saharan Africa. We analysed data for 2000–14 from the Rakai Community Cohort Study (RCCS) in Uganda, where free ART was scaled up after 2004. Using non-parametric and parametric (Weibull) survival analysis, we estimated trends in average person-years lived between exact ages 15 and 50, per capita life-years lost to HIV, and the mortality hazards of people living with HIV (PLHIV). Between 2000 and 2014, average adult life-years lived before age 50 increased significantly, from 26.4 to 33.5 years for all women and from 28.6 to 33.8 years for all men. As of 2014, life-years lost to HIV had declined significantly, to 1.3 years among women and 0.4 years among men. Following the roll-out of ART, mortality reductions among PLHIV were initially larger in women than men, but this is no longer the case.